A management of patients achieving clinical complete response after neoadjuvant therapy and perspectives: on locally advanced rectal cancer - Liu, Yu-Xin; Yang, Xin-Rong; Peng, Lan-Qing; Li, Zhuo-Hong (Frontiers in Oncology, 2025)
Neoadjuvant chemoradiotherapy (nCRT) followed by total mesorectal excision (TME) and selective use of adjuvant chemotherapy is currently considered the standard of care for locally advanced rectal cancer (LARC). Despite this, the concept of organ preservation is gradually challenging this approach. The management of complete clinical remission (cCR) lacks international consensus, leading scholars to develop their own perspectives based on well-designed studies and long-term data from large multicenter cohorts. To ensure appropriate treatment, this review focuses on the choice of neoadjuvant therapy, criteria for defining cCR, and treatment strategies for patients who achieve cCR after neoadjuvant therapy. By providing guidance on the accurate management of LARC patients after cCR, this review aims to prevent over- or under-treatment.